Effects of Cecal Cultures and Aspergillus Meal Prebiotic (Fermacto) on Growth Performance and Organ Weights of Broiler Chickens - Piray, A.H.; Kermanshahi, H.; Tahmasbi, A.M.; Bahrampour, J. (International Journal of Poultry Science, 2007)
Effects of matured caecal cultures (probiotic) of broiler breeders and Aspergillus meal prebiotic (Fermacto) on growth performance and organ weights of broiler chickens were studied from 1 to 42 days of age. 432 day-old Ross male broiler chickens were used in a 3×3 factorial arrangement with three levels of cecal cultures (0.0 , 5.0 and 10.0 mg L-1 in drinking water up to 7 days of age) and three levels of Aspergillus meal, Fermacto (0.0, 1.5 and 3.0 g kg-1) in 4 replicates (12 chickens per replicate) per treatment. The parameters, including Feed Intake (FI), Body Weight Gain (BWG) and Feed Conversion Ratio (FCR) were measured weekly during trial and weight of organs were measured at the end of the experiment. A significantly higher (p<0.01) BWG was found in 1.5 g kg-1 Fermacto-fed broilers as compared to control broilers at 14-21 days of age. The BWG was also significantly higher (p<0.01 ) in Fermacto-fed broilers as compared to control treatment at 21-28, 28-35 and 35-42 days of age, overall growing (21-42 d) and rearing periods (0-42 d). FI was significantly (p<0.01) higher for 1.5 g kg-1 Fermacto-fed broilers than that of control broilers at 14-21 and 0-21 days of age. FI was significantly greater (p<0.01 ) in Fermacto-fed broilers than that of control at 21-28, 28-35 and 35-42 days of age, during growing (21-42 d) and experimental (0-42 d) periods. FCR was improved significantly (p<0.05) by 3 g kg-1 Fermacto as compared to control at fist week. FCR was decreased significantly (p<0.05) in Fermacto-fed broilers as compared to control broilers at 21-28, 21-42 and 0-42 day of age. Relative weight of breast and thigh to body weight were significantly (p<0.01) higher in Fermacto-fed broilers as compared to control group. Cecum was significantly (p<0.01) longer in 10 mg L-1 of cecal contents and 1.5 g kg-1 Fermacto-fed broilers than those of other treatments.